2013
DOI: 10.5400/jts.2013.v18i2.125-130
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Distance Sampling and Carbon Dioxide Emission under Oil Palm Plantation

Abstract: Carbon dioxide emission on peatland under oil palm plantation were highly varied probably due to many factors involved.  The objectives of the research were to evaluate the effect of distance sampling from center of oil palm tree on Carbon dioxide flux, and  to study the factors that cause variability of carbon dioxide flux on peatland under oil palm plantation.  The study was conducted on peatland at Arang-Arang Village, Kumpek Ulu Sub-District, Muaro Jambi District, Jambi Province, on six year old oil palm p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
2
3
0
1
Order By: Relevance
“…There was a significant difference in soil CO 2 efflux between the plots at p-value < 0.001. The soil CO 2 efflux rates in this study were within the range of soil CO 2 emission reported by other studies of oil palm plantations on tropical peat swamp forest using the closed chamber technique (Ishikura et al, 2018;Hergoualc'h et al, 2017;Husnain et al, 2014;Wigena et al, 2014;Marwanto and Agus, 2014;Dariah et al, 2013;Comeau et al, 2013;IPB, 2011). Previous studies reported the total soil respiration of oil palm plantation on peat ranged between 38 mg ha -1 yr -1 (Ishikura et al, 2018) to 104 mg ha -1 yr -1 (Comeau et al, 2013).…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…There was a significant difference in soil CO 2 efflux between the plots at p-value < 0.001. The soil CO 2 efflux rates in this study were within the range of soil CO 2 emission reported by other studies of oil palm plantations on tropical peat swamp forest using the closed chamber technique (Ishikura et al, 2018;Hergoualc'h et al, 2017;Husnain et al, 2014;Wigena et al, 2014;Marwanto and Agus, 2014;Dariah et al, 2013;Comeau et al, 2013;IPB, 2011). Previous studies reported the total soil respiration of oil palm plantation on peat ranged between 38 mg ha -1 yr -1 (Ishikura et al, 2018) to 104 mg ha -1 yr -1 (Comeau et al, 2013).…”
Section: Resultssupporting
confidence: 86%
“…Studies reported by some researchers (Melling et al, 2004;2005;IPB, 2011) showed results of soil CO 2 emission measured at oil palm sites (4-5 years after planting) ranging from 56.5-85.0 mg ha -1 yr -1 . Results of soil CO 2 efflux from this study were comparable with a soil CO 2 flux measurement using the closed-chamber method with IRGA (LICOR 820) conducted by Dariah et al (2013) on 6-year-old oil palm plantation located at Jambi, Indonesia with the magnitude of 67.36 mg ha -1 yr -1 after one month of fertilisation. The average total soil respiration reported in their study ranged from 48.16-99.27 mg ha -1 yr -1 over a period of seven months of measurement.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Nilai estimasi flux CO2 yang diperoleh dari persamaan tersebut dianggap tidak relevan karena terlalu berlebih (overestimated). Hubungan antar kedua parameter tersebut juga masih menunjukkan inkonsistensi, yaitu bersifat signifikan positif (Dariah et al, 2013a;Moore dan Dalva, 1993), signifikan negatif (Hirano et al, 2014;Sarmah et al, 2014;Furukawa et al, 2005), atau tidak signifikan (Jauhiainen et al, 2008). Inkonsistensi tersebut menunjukkan lemahnya tingkat hubungan dan keterkaitan antara tinggi muka air tanah dengan flux CO2, terutama apabila nilai flux CO2 yang digunakan adalah hasil pengukuran respirasi tanah (RS).…”
Section: Pendahuluanunclassified
“…In general, peatland's GHG emissions and fire risk can be minimized if groundwater levels are maintained as shallowly as possible. Previous research have shown that maintaining a relatively shallow groundwater level would significantly reduce peatland's GHG emissions [7][8][9][10], although this condition is not suitable for all types of plants. For oil palm, for example, the ideal water level is about 50-70 cm [11].…”
Section: Introductionmentioning
confidence: 99%